Isolation, identification and pathogenicity of post-harvest decay-inducing pathogen (s) in Cucumis Africanus and Cucumis myriocarpus fruits - Mphahlele, Rebogile Ramaesele (University of Limpopo (Turfloop campus), 2011)
Crude extracts of wild watermelon (Cucumis africanus) and wild cucumber (C. myriocarpus) fruits are widely used for both medicinal and ritual purposes in South Africa. Fruits are collected fresh from the wild, but have high incidence of post-harvest decay. A study was conducted to isolate and identify the pathogen responsible for post-harvest fruit decay, followed by the pathogenicity tests. Decayed fruits were individually surface-sterilised using 0.5% NaOCl, incubated at 25ºC to allow for decay, small rotten pieces were severed and placed on solidified plates of potato dextrose agar and incubated. At harvest, seven days after incubation, isolated fungus was repeatedly cultured for 21 days for verification of diagnostic characteristics. Based on the morphological characteristics, the pathogen associated with fruit rot of both Cucumis species was identified through the assistance of an expert as Penicillium simplicissimum (Oudem) Thom. Pathogenicity results suggested that P. simplicissimum was responsible for the observed fruit decay in both species, with the higher incidence being in C. africanus, probably due to its low pH. Due to the antibiotics that P. simplicissimum releases and its reduction of medium pH, the culture retained its purity, without any contamination. In conclusion, the pathogen that induces post-harvest fruit decay in C. africanus and C. myriocarpus is P. simplicissimum, which has the ability to reduce the pH of the growing medium and also produce antibiotics.
Thesis (M.Sc. (Plant Protection )) --University of Limpopo, 2011
Keywords: Pathogenicity; Decay-inducing pathogen; Cucumis Africanus; Cucumis myriocarpus fruits; 583.63; Pathogenic fungi